Effect of salinity on removal performance and activated sludge characteristics in sequencing batch reactors. (February 2018) - Chen, Yujuan; He, Huijun; Liu, Hongyu; Li, Huiru; Zeng, Guangming; Xia, Xing; Yang, Chunping
Highlights: The effect of salinity on removal performance mainly produced in aeration phase. Salinity of as high as 20 g/L improved the settleability of activated sludge. Dehydrogenase activity of activated sludge was inhibited by increased salinity. Richness and diversity of microbial community were affected by salinity greatly. Abstract: The removal performance, activated sludge characteristics and microbial community in sequencing batch reactors (SBRs) were studied at salinity ranging from 0 to 20 g/L. Results showed that salinity deteriorated the removal performance. Removal rate of ammonium (NH4 + -N), total phosphorus (TP) and chemical oxygen demand (COD) were gradually dropped from 95.34%, 93.58% and 94.88% (0 g/L) to 62.98%, 55.64% and 55.78% (20 g/L), respectively. The removals of NH4 + -N and TP were mainly influenced during aerobic phase. Besides, salinity increased the extracellular polymeric substances (EPS) content of activated sludge, decreased the content of protein (PN) and loosely bound extracellular polymeric substances (LB-EPS) which led to better settleability of activated sludge. Moreover, salinity inhibited the dehydrogenase activity (DHA) of activated sludge. Sequence analysis illustrated Zoogloea and Thioclava were predominant at 0 and 20 g/L salinity, respectively. The difference of microbial community under high salinity was likely caused by the variation of richness.